(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to determine innovations in pregnant women’s classes at community health centers. This research uses a qualitative method with a descriptive approach. The data sources used in this research are primary data and secondary data. Data collection techniques through observation, interviews and documentation. The data source comes from 12 informants who were determined using purposive sampling. The results of the research show that the innovation in pregnant women’s class services at the Rasabou Community Health Center, Hu’u District, Dompu Regency has a relative advantage which can be seen from the aspect of change, namely helping the community, showing that there are benefits obtained through the Pregnancy Class program (2) Compatibility, namely that there is suitability or compatibility with previous innovations so that adjustments must be made (3) Complexity (Complexity) with its new nature certainly has complexity (4) Possibility of trying (Triability) The quality of an innovation is of course very important, an innovation is said to be of quality if it can provide satisfaction (5) Observability after a process or procedure is in place, of course you have made observations in the innovation.